Relevansi Nilai Atas Nilai Wajar Aset dan Liabilitas Dengan Mekanisme Good Corporate Governance Sebagai Variabel Pemoderasi - Yusifa Pascayanti; Aulia Fuad Rahman; Wuryan Andayani (Universitas Trunojoyo Madura, 2017)
This study examines the relevance of fair value of assets and liabilities and mechanisms of good corporate governance as a moderating variable by using a sample banking companies listed in Indonesia Stock Exchange from 2012 to 2014 year. The sampling method using purposive sampling and analysis of research data using Eviews. Mechanism of Good Corporate Governance in the study visits of the independent board, institutional investors and the audit committee of the company. Furthermore, this research also investigates the value relevance of accounting information such as book value, earnings, the fair value of financial assets and liabilities with a view influence on stock prices and stock returns. Ohlson Model (1995) into the measurement model used in this study, and this study examines both the measurement model Ohlson is the pricing model and the model returns to see the consistency of the study. Significant results indicate that the book value, earnings, the fair value of assets and liabilities fair value has relevance value. So we can conclude all variables affect stock prices and stock returns. In addition, Good corporate governance mechanisms able to moderate over the value relevance of book value, earnings, fair value of financial assets and liabilities fair value.